CLIL for all? A randomised controlled field experiment with sixth-grade students on the effects of content and language integrated science learning. (August 2016) - Piesche, Nicole; Jonkmann, Kathrin; Fiege, Christiane; Keßler, Jörg-U.
Abstract: Content and language integrated learning (CLIL) has been widely implemented in Europe. This article presents a randomised controlled field experiment on the effects of CLIL on students' science learning. Thirty sixth-grade intermediate-track German secondary-school classes (722 students) were randomly assigned to learn (5 lessons, 90 min each) a physics topic taught either in German or in English and German. We expected that the monolingually taught students would outperform the bilingually taught ones immediately after the intervention. For the follow-up test 6 weeks later, the same or smaller differences between the groups were expected due to the potential for a deeper processing of the subject matter in the bilingual condition. The results showed that the bilingually educated students' learning gains were smaller than the monolingually educated ones' immediately after the intervention (d = −0.21) and at follow-up (d = −0.23). The expectation of more sustainable processing was not supported. Highlights: Monolingually educated students outperformed bilingually educated ones in science. Also, bilingually educated students did not remember information better six weeks after the intervention. However, the negative effects of bilingual instruction were only small.